Epistemic communities, constructivism, and international environment al politics - Haas, Peter M. (London ; New York : Routledge, 2016)
"Epistemic Communities, Constructivism and International Environment al Politics brings together 25 years of publications by Peter M. Haas. The book examines how the world has changed significantly over the last 100 years, discusses the need for new, constructivist scholarship to u nderstand the dynamics of world politics, and highlights the role playe d by transnational networks of professional experts in global governanc e. Combining an intellectual history of epistemic communities with theo retical arguments and empirical studies of global environmental confere nces, as well as international organizations and comparative studies of international environmental regimes, this book presents a broad pictur e of social learning on the global scale. In addition to detailing the changes in the international system since the Industrial Revolution, Ha as discusses the technical nature of global environmental threats. Prov iding a critical reading of discourses about environmental security, th is book explores governance efforts to deal with global climate change, international pollution control, stratospheric ozone, and European aci d rain. With a new general introduction and the addition of introductor y pieces for each section, this collection offers a retrospective overv iew of the author's work and is essential reading for students and scho lars of environmental politics, international relations and global poli tics"--
Introduction : ReConstructing Epistemic Communities : Ontology & His torical Background -- Transnational Flows and the Transformation of Int ernational Relations, prepared for the American Association for the Adv ancement of Science, February. 1988 -- The Capacity of International In stitutions to Manage Bhopal-like Problems, in Sheila Jasanoff (ed.) Lea rning from Disaster: Policy Consequences of Bhopal Philadelphia: Univer sity of Pennsylvania Press, pp. 225-247. 1994 -- Introduction : Epistem ic Communities and International Policy Coordination, International Org anization Vol. 46 No. 1 Winter, pp. 1-37,1992 -- Constructing Environme ntal Security from Resource Scarcity, Global Environmental Politics Vol . 2 No 1, pp. 1-19. 2002 -- Social Constructivism and the Evolution of Multilateral Environmental Governance, in Aseem Prakash and Jeffrey A. Hart (eds.) Globalization and Governance, Routledge, pp. 103-133 -- Pro spects for Effective Marine Governance in the NW Pacific Region, Marine Policy, Volume 24, No. 4, July, pp. 341-8; and Letter to the Editor, M arine Policy, Volume 24, No. 6, December pp 499-500. 2000 -- Epistemic Communities and International Environmental Law, in Daniel Bodansky, Ju tta Brunnee and Ellen Hey eds. The Oxford Handbook of International Env ironmental Law Oxford: Oxford University Press. 2007 -- UN Conferences and Constructivist Governance of the Environment, Global Governance Vol . 8 No 1, pp. 73-91. 2002 -- International Institutions and Social Lear ning in the Management of Global Environmental Risk, Policy Studies Jou rnal Vol.. 28, no. 3, pp 558-575. 2000 -- Addressing the Global Governa nce Deficit, Global Environmental Politics Vol 4 No 4 pp 1-19. 2004 -- Peter M. Haas and Ernst B. Haas, Learning to Learn, Global Governance 1 :3 (1995) pp 255-284 -- Choosing to Comply, in Dinah Shelton Ed. Compli ance with Soft Law Oxford University Press pp 43-64. 2000 -- Evaluating the Effectiveness of Marine Governance, in Chua Thia-Eng, Gunnar Kulle nberg, and Danilo Bonga eds. Securing the Oceans Quezon City, Phillipin es: Global Environment Facility/United Nations Development Programme/In ternational Maritime Organization Regional Programme on Building Partne rships in Environmental Management for the Seas of East Asia (PEMSEA) a nd the Nippon Foundation. 2008 -- When Does Power Listen to Truth, A Co nstructivist Approach to the Policy Process, Journal of European Public Policy Vol 11 No 4 pp 569-592. 2004 -- Peter M. Haas and Casey Stevens , Organized Science, Usable Knowledge, and Multilateral Environmental G overnace, in Rolf Lidskog and Goran Sundquist eds. Governing the Air: S cience-Policy Interactions in International Air Policy Work MIT Press 2 011 -- Promoting Knowledge Based International Governance for Sustaina ble Development, in Sophie Thoyer and Benoit Martimort-Asso eds. Partic ipation for Sustainability in Trade Brookfield, VT: Ashgate Publishing -- The Global Spreading of Ideas, WZB-Mittelungen Heft 127 March pp 40- 42.
Keywords: Environmental policy -- International cooperation; Environmental protection -- International cooperation; Global environmental change -- International cooperation; POLITICAL SCIENCE / International Relations / General; POLITICAL SCIENCE / Public Policy / Environmental Policy; POLITICAL SCIENCE / General